(Identification and Analysis Of Competitiveness Of Marine Products Industry in Tegal Regency, Central Java) - Sudibyo, Agus; Dwi Erlina, Mei; -, Winiarti (Balai Besar Industri Agro, 2006)
Study on identification and analysis of competitiveness for the marine-fisheries product industry in Tegal regency,Central of Java has been conducted.The methods used of this study was using descriptive and system approach that included identification of marine fisheries potential,selection of potential commodities,determination of marine-fisheries based industry specially products and feasibility study on the development of those product.The process selecting potential commodities and determination of the marine-fisheries based industrycompetitiveness product were analysis by using Analytical Hierarchy Process(AHP)approach,while feasibility was analysis by using three econemic indicates in terms of B/C ratio,NPV and IRR.The results showed that based on the all criteria desigeneed in identification and selecting of the marine-fisheries based industry competitiveness products,it was indicated that the availability and economic value of raw material were the important factor in the evaluation of potential alternative commodity.Meanwhile,technology capability,value added,quality and continues supply of raw materials and market the marine-fisheries based industry specially products.Based on the adjustments of weighting and scoring to the various commodities and processing technologies resulted that salted-dried anchoy and boiled-salted scads were the most prospective marine-fisheries product that can be developed as specially product for Tegal regency.Financial analysis lso show that the two products were very feasible financially.Â